Iōannou Skylitsē Chronographias synecheia. - Scylitzes, John, active 1081.
1 online resource.
Keywords: “The years before and after the battle of Manzikert (1071) mark a turning point in the history of the Byzantine Empire. The invasions of the Seljuk Turks in the east and the encroachment of the Normans from the west altered the balance of power in the eastern Mediterranean and forced the Byzantines to confront new threats to their survival. These threats came at a time when internal rivalries made an effective military response all but impossible and led to a significant transformation of the Byzantine polity under the Komnenoi. The Continuation of the Chronicle of John Skylitzes, now translated for the first time, provides a contemporary view of these troubled times. An extension of the principal source for the middle Byzantine period, and a subtle reworking of the History of Michael Attaleiates, the Continuation offers a high court official's narrative of the events and personages that shaped the course of Byzantine history on the eve of the Crusades.“.